FEATURES OF DEVELOPING A DIGITAL MARKETING STRATEGY IN AN ELECTRONIC BUSINESS ORGANIZATION - BOLOTNA, Oksana; LIASHEVSKA, Viktoriia; SIVKIV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article analyzes the fundamental aspects of constructing a digital marketing strategy in organizations focused on electronic business. The impact of contemporary trends and challenges in electronic business on the strategic thinking of enterprises is described, particularly in the context of rapid technological changes and increased competition. The author explores key aspects of digital marketing strategy, defining their role in achieving success in electronic business. Specifically, the transition from traditional marketing methods to the use of online tools and internet platforms is examined. Special attention is given to creating an effective company image in the online environment and developing strategies aimed at building consumer trust. Proposed practical recommendations focus on improving segmentation, integrating electronic marketing, and creating personalized marketing messages for effective interaction with digital consumers. Proper construction of a digital marketing strategy enables the efficient utilization of digital marketing tools and internet platforms to enhance interaction, attract new customers, and retain existing ones. The overall goal is to improve the efficiency of marketing strategies, ensure high customer satisfaction, and increase the profitability of electronic business. This information can be utilized by top management, marketing departments, and electronic business specialists for the development and enhancement of marketing strategies. The emphasis is placed on the fact that an effective digital marketing strategy is a key success factor for organizations operating in the electronic business sector, highlighting the importance of continual adaptation to changes in the online environment to secure a sustainable competitive advantage through the use of personalized approaches and innovations.
Keywords: digital marketing; electronic business; marketing strategies